High-flux positron generation via the ultra-intense laser irradiating density-modulated plasmas - Liu, Jian-Xun; Gao, Ting; Wang, Xu; Jin, Hong-Bin; Deng, Wei-Qiang; Liu, Tai-Yang; Yu, Tong-Pu (Frontiers in Physics, 2023)
To investigate plasma density on the Breit-Wheeler positron generation, comparative study of four plasma targets is performed via the PIC code EPOCH. When an ultra-intense laser (2.8×〖10〗^23 Wcm^(-2)) is incident, more positrons with high energy are generated in the increasing density plasmas. The positron yield is already 1.5×〖10〗^8 with a cutoff energy of 2 GeV at t=37T_0. It is demonstrated that increasing density plasmas will enhance gamma photon radiation and positron generation. In increasing density plasmas, under dense plasmas are in favor of electron acceleration, and over dense plasmas will induce laser reflection. Cross sections of the Compton back-scattering and the BW positron generation are both increased via high energy electrons colliding with the reflected laser. In addition, increasing the laser intensity will directly enhance positron generation. This investigation will further facilitate high flux positron generation and application.